Analisis Penggunaan Tata Bahasa Indonesia dalam Penulisan Ragam Kalimat: Studi Kasus Pemelajar Kelas 11 SMA Cristal Dili - Yutriani Andhika (Jurnal Bahasa Indonesia bagi Penutur Asing, 2019)
Writing a variety of sentences in Bahasa Indonesia must be following Indonesian grammar rules. The purpose of this writing is to describe the simple Indonesian grammar, as well as to see its implementation on the teaching of class 11 BIPA in Cristal Dili High School. Analysis of the use of Indonesian grammar in writing a variety of sentences is done by a qualitative descriptive method. As a tool to describe Indonesian grammar used in Indonesian grammar according to the rules of the grammar of Bahasa Indonesia, enhanced spelling, and dictionary of the Indonesian language. The Indonesian standard of writing sentences includes proper word selection, effective sentence, punctuation usage, and capitalization. The results showed that the infirmity of writing sentences using Bahasa Indonesia was the fault of ineffective punctuation, diction, and sentences.